2003
DOI: 10.3184/030823403103172823
|View full text |Cite
|
Sign up to set email alerts
|

Solvent free Oxidation of Thiols by (NH4)2Cr2O7 in the Presence of Mg(HSO4)2 and wet SiO2

Abstract: A very simple and mild reaction for the efficient coupling of thiols by ammonium dichromate (ADC) in the presence of Mg(HSO4)2 and wet SiO2, under solvent free conditions, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[31][32][33] Along these lines, we found that Zr(HSO 4 ) 4 can be used as an efficient reagent for the cleavage of C=N bonds in the presence of wet SiO 2 . [31][32][33] Along these lines, we found that Zr(HSO 4 ) 4 can be used as an efficient reagent for the cleavage of C=N bonds in the presence of wet SiO 2 .…”
mentioning
confidence: 75%
“…[31][32][33] Along these lines, we found that Zr(HSO 4 ) 4 can be used as an efficient reagent for the cleavage of C=N bonds in the presence of wet SiO 2 . [31][32][33] Along these lines, we found that Zr(HSO 4 ) 4 can be used as an efficient reagent for the cleavage of C=N bonds in the presence of wet SiO 2 .…”
mentioning
confidence: 75%
“…A combination of (NH 4 ) 2 Cr 2 O 7 , Mg(HSO 4 ) 2 and wet SiO 2 was also used for the oxidation of thiols to disulfides (Scheme 40) [59]. Comparison between the obtained results cleared that under solvent-free conditions, the reactions were completed at shorter reaction times with higher yields of the products.…”
Section: Oxidation Reactionsmentioning
confidence: 97%